Role of STAT‐1 and STAT‐3 in ischaemia/reperfusion injury - Stephanou, A. (J Cell Mol Med, 2007)
Ischaemia/reperfusion (I/R) injury results in the death of irreplaceable cardiac myocytes by a programme cell death or apoptosis. The signal transducers and activators of transcription (STAT) factors function as modulators of cytokine signaling and sensors responding to cellular stress. Interestingly, many studies have demonstrated that although they have a similar structural organization, STAT‐1 and STAT‐3 have apposing effects on processes such as differentiation or apoptosis. For example, STAT‐1 has been shown to induced apoptosis, whilst STAT3 is able protect cardiac myocytes following ischaemia/reperfusion (I/R) injury. Many of the effects of STAT‐1 and STAT‐3 involve the direct binding to DNA and transcriptional activation of target genes. However, recent studies have shown that for STAT‐1 some of its effects appear not to require DNA binding. For example, induction of apoptosis by STAT‐1 can be produced by the C‐terminal activation domain in the absence of the DNA binding domain. This therefore, appears to involve a co‐activator effect in which STAT‐1 is recruited to DNA via a DNA‐bound transcription factor. In this regard, it is of interest that STAT‐1 but not STAT‐3 has been shown to interact with p53 and enhance its growth arrest and apoptosis‐ inducing properties. Hence, the finding that STAT‐1 and STAT‐3 can modulate the apoptotic programme both by direct DNA binding or via a co‐activator mechanism and despite their very similar structures, suggests that these related factors may be therapeutic targets against the damage myocardium following I/R injury. Recently, we reported that the polyphenolic agent epigallocatechin‐3‐gallate (EGCG), a major constituent of green tea and a potent inhibitor of STAT‐1 activation, protects the myocardium against I/R injury.